Desenvolvimento de método para determinação de resíduos de agrotóxicos em água mineral engarrafada produzida em Sergipe - Santos, Bárbara Luisa Soares dos Reis (2018)
Bottled mineral water is a widely consumed product in Brazil because it is considered a reliable source of drinking water. On the other hand, there is the great use of pesticides, which can reach and contaminate groundwater, the main source of mineral water. The present research had the objective of developing a method for the determination of residues of pesticides in bottled mineral water, using the technique of solid phase extraction with alternative adsorbent to the base of graphene oxide and liquid chromatography/mass spectrometry. For that, tests were performed to optimize the instrumental and extraction conditions for the analysis of 6 pesticides (alachlor, atrazine, carbaryl, carbofuran, pyrimicarb and endosulfan sulfate). The analytes were extracted with graphene oxide and a mixture of methanol and acetonitrile, presenting satisfactory recovery values (76 ± 1.6 and 100 ± 2.4%) in a concentration range of 0.5 to 2.5 μg L-1. In optimal conditions good linearity and sensitivity were obtained in a range of 1 to 1000 μg L-1 with determination coefficients above 0.99. The relative standard deviations for triplicate determinations were less than 12% and the limits of detection and quantification were in the range of 0.0003-0.017 μg L-1 0.001-0.05 μg L-1, respectively. The proposed method was applied in the determination of pesticides residues in bottled mineral water produced in Sergipe.